ANALISIS RISIKO KEDARURATAN BAHAN BERBAHAYA DAN BERACUN (B3) DI KOTA BALIKPAPAN - Muhammad Isradi Zainal; Fatma Lestari; Iin Pratamasari; Widya Mulya; Lina Yuliana (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine the level of risk of hazardous and toxic materials in the city of Balikpapan. The method used is a risk assessment carried out by looking at the potential hazards and the level of exposure. Referring to the Regulation of the Minister of the Environment Number 74 of 2019 concerning the Emergency Program for B3 & or B3 Waste Management, the data and information needed for risk assessment are: type of B3 Management activity, type of industry, B3 classification, amount of B3, potential threat to the safety of human life ; and potential threats to environmental functions. The results showed that the average B3 emergency risk value in the Balikpapan Energy, Oil and Gas Mining sector from the KLHK and Ministry of Manpower approaches was 32.87 and 32.81, respectively; which means moderate risk. The dominant types of B3 are flammable and corrosive and most of the B3 are B3 category 1. The average B3 emergency risk value in the Balikpapan Water Supply Sector from the KLHK and Ministry of Manpower approaches is 24, which means low risk. The dominant type of B3 is corrosive and most of the B3 is B3 category 1. The average level of B3 risk in the city of Balikpapan as a whole from the KLHK and Ministry of Manpower approaches is 31.56 and 31.51 (medium). If the highest category is taken, the risk level for B3 waste is at a low level. Potential for B3 emergencies: B3 spills, fires, explosions, exposure to humans and environmental pollution.